Microbiota-Host-Irinotecan Axis: A New Insight Toward Irinotecan Chemotherapy - Yue, Bei; Gao, Ruiyang; Wang, Zhengtao; Dou, Wei (Frontiers in Cellular and Infection Microbiology, 2021)
Irinotecan (CPT11) and its active metabolite ethyl-10-hydroxy-camptothecin (SN38) are broad-spectrum cytotoxic anticancer agents. Both cause cell death in rapidly dividing cells (e.g., cancer cells, epithelial cells, hematopoietic cells) and commensal bacteria. Therefore, CPT11 can induce a series of toxic side-effects, of which the most conspicuous is gastrointestinal toxicity (nausea, vomiting, diarrhea). Studies have shown that the gut microbiota modulates the host response to chemotherapeutic drugs. Targeting the gut microbiota influences the efficacy and toxicity of CPT11 chemotherapy through three key mechanisms: microbial ecocline, catalysis of microbial enzymes, and immunoregulation. This review summarizes and explores how the gut microbiota participates in CPT11 metabolism and mediates host immune dynamics to affect the toxicity and efficacy of CPT11 chemotherapy, thus introducing a new concept that is called “microbiota-host-irinotecan axis”. Also, we emphasize the utilization of bacterial β-glucuronidase-specific inhibitor, dietary interventions, probiotics and strain-engineered interventions as emergent microbiota-targeting strategies for the purpose of improving CPT11 chemotherapy efficiency and alleviating toxicity.